Investigating the effect of different loading densities on selected properties of dried coffee using a GHE dryer - Menya, E.; Komakech, A. J. (Agric Eng Int: CIGR Journal, 2013)
Despite coffee being one of the leading cash crops in Uganda contributing 20%-30% of the total export earnings, it is mainly dried on bare earth surfaces hence its drastic decline in quality. A possible alternative solution is utilization of the greenhouse effect (GHE) solar dryer. This research was aimed at investigating the effect of different loading densities on selected properties of dried coffee using a GHE dryer that was designed and constructed at Makerere University Agricultural Research Institute Kabanyolo (MUARIK). The research involved determining the drying time for the loading densities of 5, 10 and 20 kg m-2 as well as analyzing the coffee quality at the end of the drying period. Three experimental runs were set up in the months of June and July which experienced average ambient temperature of 23.28 (±2.33)oC and average dryer temperature of 35.68 (±13.85)oC. The average drying time for the freshly harvested Robusta coffee at 61.3 (±1.36)% wb was 10 days for 5 kg m-2, 11 days for 10 kg m-2 and 12 days for 20 kg m-2. The loading of 20 kg m-2 resulted into an even roast with fair+ for body and flavour, while 5 and 10 kg m-2 loadings resulted into a silver skin roast with fair body and flavour. For this particular research, the loading density of 20 kg m-2 yielded the best results from the coffee quality analysis. The loading densities of 5 kg m-2 and 10 kg m-2 could not yield best results due to case hardening of the outer surfaces of the coffee beans which compromised the body and flavour of the coffee.
Keywords: greenhouse effect; solar dryer; loading densities; coffee quality; drying time